Pengaruh Kesadaran Wajib Pajak, Kualitas Pelayanan dan Pengetahuan Perpajakan Terhadap Kepatuhan Wajib Pajak Dengan Sanksi Perpajakan Sebagai Variabel Moderating (Studi Empiris Pada Wajib Pajak Orang Pribadi Di Kota Mataram) - Nadhila Ghassani (Universitas 17 Agustus 1945 Surabaya, 2019)
This research aims to analyze the factors that influence of taxpayers awareness, qualityof services, tax knowledge, tax sanctions of taxpayers compliance. The sample of thisresearch are individual taxpayers that taken randomly in Mataram City. This researchis also using tax sanctions as a moderating variable.Â The respondents from thisresearch are 150 respondents. Data analysis method that used in this research areModerated Regression Analysis (MRA) and performed using SPSS for Windows.Theresults of this research indicated that awareness of taxpayers, quality of services, taxknowledge have a positive and significant influence of taxpayers compliance. Taxsanctions variable as a pure moderator that strenghten the relationship betweendependent variable and independent variables.Keyword: Taxpayers Awareness, Quality of services, Tax knowledge, Tax sanctions,Taxpayers compliance